Quarter-dose quadruple combination therapy for initial treatment of hypertension: placebo-controlled, crossover, randomised trial and systematic review. Issue 10073 (11th March 2017) - Chow, Clara K; Thakkar, Jay; Bennett, Alex; Hillis, Graham; Burke, Michael; Usherwood, Tim; Vo, Kha; Rogers, Kris; Atkins, Emily; Webster, Ruth; Chou, Michael; Dehbi, Hakim-Moulay; et al.
Summary: Background: Globally, most patients with hypertension are treated with monotherapy, and control rates are poor because monotherapy only reduces blood pressure by around 9/5 mm Hg on average. There is a pressing need for blood pressure-control strategies with improved efficacy and tolerability. We aimed to assess whether ultra-low-dose combination therapy could meet these needs. Methods: We did a randomised, placebo-controlled, double-blind, crossover trial of a quadpill—a single capsule containing four blood pressure-lowering drugs each at quarter-dose (irbesartan 37·5 mg, amlodipine 1·25 mg, hydrochlorothiazide 6·25 mg, and atenolol 12·5 mg). Participants with untreated hypertension were enrolled from four centres in the community of western Sydney, NSW, Australia, mainly by general practitioners. Participants were randomly allocated by computer to either the quadpill or matching placebo for 4 weeks; this treatment was followed by a 2-week washout, then the other study treatment was administered for 4 weeks. Study staff and participants were unaware of treatment allocations, and masking was achieved by use of identical opaque capsules. The primary outcome was placebo-corrected 24-h systolic ambulatory blood pressure reduction after 4 weeks and analysis was by intention to treat. We also did a systematic review of trials evaluating the efficacy and safety of quarter-standard-dose blood pressure-lowering therapy against placebo. This trial is registered with the Australian New Zealand Clinical Trials Registry, number ACTRN12614001057673. The trial ended after 1 year and this report presents the final analysis. Findings: Between November, 2014, and December, 2015, 55 patients were screened for our randomised trial, of whom 21 underwent randomisation. Mean age of participants was 58 years (SD 11) and mean baseline office and 24-h systolic and diastolic blood pressure levels were 154 (14)/90 (11) mm Hg and 140 (9)/87 (8) mm Hg, respectively. One individual declined participation after randomisation and two patients dropped out for administrative reasons. The placebo-corrected reduction in systolic 24-h blood pressure with the quadpill was 19 mm Hg (95% CI 14–23), and office blood pressure was reduced by 22/13 mm Hg (p<0·0001). During quadpill treatment, 18 (100%) of 18 participants achieved office blood pressure less than 140/90 mm Hg, compared with six (33%) of 18 during placebo treatment (p=0·0013). There were no serious adverse events and all patients reported that the quadpill was easy to swallow. Our systematic review identified 36 trials (n=4721 participants) of one drug at quarter-dose and six trials (n=312) of two drugs at quarter-dose, against placebo. The pooled placebo-corrected blood pressure-lowering effects were 5/2 mm Hg and 7/5 mm Hg, respectively (both p<0·0001), and there were no side-effects from either regimen. Interpretation: The findings of our small trial in the context of previous randomised evidence suggest that the benefits of quarter-dose therapy could be additive across classes and might confer a clinically important reduction in blood pressure. Further examination of the quadpill concept is needed to investigate effectiveness against usual treatment options and longer term tolerability. Funding: National Heart Foundation, Australia; University of Sydney; and National Health and Medical Research Council of Australia.